On the effect of interfacial patterns on energy dissipation in plastically deforming adhesive bonded ductile sheets. (1st August 2020) - Pascuzzo, Arturo; Yudhanto, Arief; Alfano, Marco; Lubineau, Gilles
Abstract: Toughening of brittle adhesive joints is a topic of great interest for the fabrication of layered structures. Recent experimental work by the authors indicated that spatially varying interface properties ( i.e ., patterned interfaces obtained using laser irradiation) could tune energy dissipation in plastically deforming adhesive joints. In this study, we use a cohesive zone approach to ascertain the interplay between fracture process zone size and pattern geometry on the overall work of separation. The analysis is carried out in the context of the elasto-plastic peeling response of adhesive bonded ductile thin sheets. The mating surfaces of the adherents feature alternating strips with strong and weak cohesive properties. Our finite element study shows that a careful choice of pattern length-scales, which requires a small area fraction of surface pre-treatment, allows to achieve a step-like increase in peel load and absorbed energy in otherwise brittle adhesive joints.